Self-neglect : a practical approach to risks and strengths assessment. - Britten, Shona (Critical skills for social work., 2018)
A practical intervention framework and guide in Risks & Strengths Assessment in self-neglect for support staff who are working with adults who self-neglect or may be at risk of self-neglecting in the future.